Physical and protein characteristics of rabbit meat fed multinutrient hay waffles - Gallusia M.N. Isty; Okti Widayati; Bangkit L. Syaefullah (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2026)
The quality of the meat generated as a byproduct of rabbit fattening is related to the feed quality. The physical qualities of meat are one of the feed-related elements that customers evaluate when purchasing meat. Colour, tenderness, pH, water retention capacity, and cooking loss are all important markers of meat quality. The goal of this study was to look at the physical characteristics of rabbit meat given hay-based multinutrient waffles. During a two-month feeding trial, 18 female Hycole rabbits were separated. The characteristics studied included pH, softness, cooking loss, protein content, and water holding capacity. Data were examined using SPSS, and if significant differences were found, the Dunnett test was used to do additional analysis. The findings revealed that feeding hay-based multinutrient waffles had no significant effect on pH or cooking loss, but had a substantial impact on softness, protein content, and WHC. since a result, using hay-based multinutrient waffles in rabbit diets may be regarded economically viable, since it maintains meat quality comparable to commercial pellets and forage.